Immunobiotic lactobacilli reduce viral-associated pulmonary damage through the modulation of inflammation-coagulation interactions - Zelaya, María Hortensia del Rosario (2014)
The exacerbated disease due to immune- and coagulative-mediated pulmonary injury during acute respiratory viruses infection results in severe morbidity and mortality. Identifying novel approaches to modulate virus-induced inflammation-coagulation interactions could be important alternatives for treating acute respiratory viruses infections. In this study we investigated the effect of the probiotic strain Lactobacillus rhamnosus CRL1505 on lung TLR3-mediated inflammation, and its ability to modulate inflammation-coagulation interaction during respiratory viral infection. Our findings reveal for the first time that a probiotic bacterium is able to influence lung immune-coagulative reaction triggered by TLR3 activation, by modulating the production of proinflammatory and anti-inflammatory cytokines as well as expression of tissue factor and thrombomodulin in the lung. We also demonstrated that the preventive treatment with the probiotic bacteria beneficially modulates the fine tune balance between clearing respiratory viruses (respiratory syncytial virus and influenza virus) and controlling immune-coagulative responses in the lung, allowing normal lung function to be maintained in the face of a viral attack. Our data also pinpoint a crucial role for IL-10 in the immune protection induced by L. rhamnosus CRL1505 during respiratory viral infections. These observations might be helpful to propose new preventive or therapeutic approaches to better control virus-inflammatory lung damage using probiotic functional foods.